2021
DOI: 10.1007/s11764-021-01036-4
|View full text |Cite
|
Sign up to set email alerts
|

Is accurate routine cancer prognostication psychologically harmful? 5-year outcomes of life expectancy prognostication in uveal melanoma survivors

Abstract: Purpose Prognostication in cancer is growing in importance as increasingly accurate tools are developed. Prognostic accuracy intensifies ethical concerns that a poor prognosis could be psychologically harmful to survivors. Uveal melanoma (UM) prognostication allows survivors to be reliably told that life expectancy is either normal (good prognosis) or severely curtailed because of metastatic disease (poor prognosis). Treatment cannot change life expectancy. To identify whether prognosis is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…Research has shown that the majority of melanoma patients wish to have full information about their diagnosis and prognosis [ 18 ] but there is very little exploring the psychological impact of prognosis on patients with Stage I/II cutaneous melanoma. There are studies with patients with uveal melanoma and the most recent, a five-year study of 708 survivors with a poor or good prognosis and those who had declined testing, reports ‘that harm accruing from a poor prognosis was statistically significant over 5 years but did not exceed general non-cancer population norms.’ [ 19 ]. The authors conclude that clinicians should inform patients that there may be adverse psychological consequences in the event of a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the majority of melanoma patients wish to have full information about their diagnosis and prognosis [ 18 ] but there is very little exploring the psychological impact of prognosis on patients with Stage I/II cutaneous melanoma. There are studies with patients with uveal melanoma and the most recent, a five-year study of 708 survivors with a poor or good prognosis and those who had declined testing, reports ‘that harm accruing from a poor prognosis was statistically significant over 5 years but did not exceed general non-cancer population norms.’ [ 19 ]. The authors conclude that clinicians should inform patients that there may be adverse psychological consequences in the event of a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were offered prognostication at a single unit that has offered prognoses for over 15 years 10,34,42 . Transfer of the UM paradigm to other cancers needs to be handled carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes of a good prognosis do not differ from no prognosis. Distress in the poor prognosis group may not significantly exceed healthy age and gender‐matched population means 10,34 . Population characteristics mask individual variability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations